What does research say about the texts we use in elementary school?. (May 2022) - Smith, Kristin Conradi; Hiebert, Elfrieda H.
Much of the attention given to literacy, of late, has focused on ensuring that students can read, without consideration to what they are given to read. Kristin Conradi Smith & Elfrieda H. Hiebert discuss four general aspects of the texts used in elementary classrooms – text complexity, text type (narrative versus informational), text format (paper versus screen), and diversity of people presented in the text. They review recent research on each of these text characteristics and then make suggestions for how to apply the research in the classroom .